2021
DOI: 10.3389/fevo.2020.616562
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Glacier Retreat Are Uneven Between Plant Species

Abstract: Glaciers are retreating worldwide, exposing new terrain to colonization by plants. Recently-deglaciated terrains have been a subject of ecological studies for a long time, as they represent a unique natural model system for examining the effects of global warming associated with glacier retreat on biodiversity and the spatio-temporal dynamic of communities. However, we still have a limited understanding of how physical and biotic factors interactively influence species persistence and community dynamics after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 63 publications
2
43
0
Order By: Relevance
“…Microbes may be more responsive to other environmental factors that may act on short term fluctuations such as temperature, which is equally well predicted by the compositions of bacteria, fungi and plants suggesting its common importance in defining the niche of all taxa. Previous studies demonstrated that plants and microbes from different origins may respond to increased temperature variously, thus we may infer that climate change will shift the interactive patterns between species (Rasmussen et al, 2019;Rudgers et al, 2020;Losapio et al, 2021). In addition, pH was better predicted by bacteria and fungi than by plants, indicating that pH is affecting soil microbes more than plants, which is in agreement with previous studies illustrating the importance of pH in affecting microbial communities (Knelman et al, 2012;Shen et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Microbes may be more responsive to other environmental factors that may act on short term fluctuations such as temperature, which is equally well predicted by the compositions of bacteria, fungi and plants suggesting its common importance in defining the niche of all taxa. Previous studies demonstrated that plants and microbes from different origins may respond to increased temperature variously, thus we may infer that climate change will shift the interactive patterns between species (Rasmussen et al, 2019;Rudgers et al, 2020;Losapio et al, 2021). In addition, pH was better predicted by bacteria and fungi than by plants, indicating that pH is affecting soil microbes more than plants, which is in agreement with previous studies illustrating the importance of pH in affecting microbial communities (Knelman et al, 2012;Shen et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…In the predicted scenario of climate warming, a high turnover rate in mountain environments is expected [ 94 ]. Models predict that plant diversity will initially increase with the retreat of glaciers because of the upward migration of lower-elevation species.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that, as the ice retreats, not all the species associated with glaciers will be able to migrate and colonize suitable habitats nearby (Körner, 2005). For example, Losapio et al (2021) showed that vascular plant diversity would decrease with glacier extinction and about one fourth of plant species would become locally extinct. Losapio et al (2021) further indicated that those plants most in danger from disappearing glaciers are those of the pioneer communities, which, because these are often facilitators of subsequent communities, will lead to extinction cascades.…”
Section: Threats To the Lichen Biotamentioning
confidence: 99%
“…For example, Losapio et al (2021) showed that vascular plant diversity would decrease with glacier extinction and about one fourth of plant species would become locally extinct. Losapio et al (2021) further indicated that those plants most in danger from disappearing glaciers are those of the pioneer communities, which, because these are often facilitators of subsequent communities, will lead to extinction cascades. Cryptogams often dominate these pioneer communities and so these would be disproportionally and negatively affected by glacier extinctions.…”
Section: Threats To the Lichen Biotamentioning
confidence: 99%